2015
DOI: 10.1021/acs.jafc.5b01453
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol in Olive Fruit. Changes during Ripening

Abstract: Ethanol is one of the precursors of ethyl esters, the virgin olive oil quality parameter for the "extra" category recently adopted by the European Union and International Olive Oil Council. Although ethyl ester content has great importance for virgin olive oil classification, the origin of ethanol is not clear. A possible source of ethanol may be the olive fruit itself while it remains on the tree. Variation of fruit ethanol content during ripening was studied for three different olive cultivars: 'Picual', 'Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 10 publications
(22 reference statements)
4
33
2
8
Order By: Relevance
“…Acetaldehyde increased in reduction capacity in the fermentation pathway. Beltrán, et al [63] observed the accumulation of both ethanol and acetaldehyde in olive fruit during maturation, although ethanol showed a more rapid increase.…”
Section: Resultsmentioning
confidence: 99%
“…Acetaldehyde increased in reduction capacity in the fermentation pathway. Beltrán, et al [63] observed the accumulation of both ethanol and acetaldehyde in olive fruit during maturation, although ethanol showed a more rapid increase.…”
Section: Resultsmentioning
confidence: 99%
“…However, Beltran et al showed that the origin of ethanol is unclear, and the olive fruit itself is a possible source. According to the latter study, ethanol accumulates in olive fruit during ripening due to the activity of the enzyme alcohol dehydrogenase during the synthesis of anaerobic metabolites (including ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work has found that, in these conditions, oxygen in the headspace is naturally consumed by the paste and, at the same time, a huge amount of carbon dioxide accumulates in the sealed chamber . Following the work of Beltran et al and the hypothesis that ethanol formation in olive fruit is due to enzymatic activity, the accumulation of headspace ethanol during malaxation in sealed conditions is investigated in a series of trials, in an attempt to better understand the olive/ethanol association.…”
Section: Introductionmentioning
confidence: 99%
“…Conte et al described the formation of ethyl esters during oil conservation. Ethyl esters can be formed by direct esterification of free fatty acids or by transesterification of fatty acids from triacylglycerides as described by Biedermann et al Their alcoholic precursor – ethanol – may be synthesized in the own olive fruit whereas it remains on the tree, but any alteration of the fruit can result in fruit enzyme activation or attack by microorganisms because of the loss of fruit integrity during its period on the ground. Furthermore, an increase in ethanol content and free acidity, although values were always below the regulated limits, may induce the synthesis of ethyl esters in VOO.…”
Section: Introductionmentioning
confidence: 99%